Pengaruh Intervensi Food Safety Awareness terhadap Pengetahuan, Sikap, dan Praktik Siswa Sekolah Dasar: Studi Pre-Eksperimental di SD Negeri Gajahmungkur 01 - Farida Rahmawati; Zulfa Ida Eliza; Salwa Aldama Savika; Firsta Khanania Mayda; Firannisa Rafa Adinda I.; Ravenska Praditya Ramadhani P.; Athaya Risqullah Qurratu Aini (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Food safety among elementary school children remains a significant public health concern due to the increased risk of foodborne diseases caused by unhygienic food consumption and poor hygiene behavior. This study aimed to analyze the effect of a food safety awareness intervention on students’ knowledge, attitudes, and practices regarding food hygiene and clean healthy living behavior at SD Negeri Gajahmungkur 01 Semarang. The study employed a quantitative pre-experimental design using a one group pre-test post-test approach involving 81 students from grades IV, V, and VI selected through total sampling. The intervention consisted of food safety education, germ transmission simulations, safe snack identification, and handwashing demonstrations. Data were collected using structured questionnaires and analyzed using the Wilcoxon Signed Rank Test. The findings demonstrated significant improvements across all variables after intervention (p<0.05). The highest increase occurred in grade IV students, particularly in attitudes and practices (53.6%). Interactive and practice-based educational methods contributed to behavioral adaptation and strengthened preventive hygiene habits among elementary school students.